Development and validation of the Mindful Parenting in Infancy Scale (MPIS). (16th June 2021) - Gartstein, Maria A.
Abstract: Although mindfulness in parenting has been recognized as important for some time, there is a dearth of measurement tools, especially for caregivers of infants. Two studies were conducted: (1) developing and providing an initial psychometric evaluation of the Mindful Parenting in Infancy Scale (MPIS) and (2) reproducing initial findings with an independent sample of infants and caregivers. In Study 1, 37 caregivers of infants (3–12 months of age) responded to MPIS, providing indicators of parenting stress and infant temperament. Study 2 caregivers ( N = 57) responded to identical measures, with infant electroencephalogram (EEG) recorded during the Still Face Procedure, along with a baseline condition. Study 1 results indicated good internal consistency, with Study 2 providing additional support for reliability. Correlations with parenting stress markers were also significant across both investigations, indicative of greater stress with lower levels of mindfulness. A number of correlations with temperament scores were also significant, and in the hypothesized direction, across both studies. Importantly, the MPIS score was predictive of infant frontal EEG asymmetry in a path model examined in the context of Study 2. Thus, the present investigation provides support for MPIS as a promising brief measurement tool based on results obtained with two independent samples.